Strengthening the resilience of the MICE industry: Navigating budgetary dependency, gender parity, and environmental sustainability - Ediyah Ediyah Pujiastuti (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: The tourism sector encompasses MICE (Meetings, Incentives, Conferences, and Exhibitions). Human resources, hotels, restaurants, travel agencies, exhibition contractors, and audio, sound, and lighting equipment are just a few of the many cross-sectoral companies that operate in this area. Along with having a positive economic impact, the MICE sector helps Indonesia's tourism industry. Every MICE event in Indonesia draws thousands of participants from both foreign and indigenous nations. The opportunity to visit neighboring tourist destinations is offered to participants. This will increase economic output, create jobs, and broaden Indonesia's travel offerings internationally. Furthermore, the MICE events help to improve Indonesia's global connectedness and contribute to the enhancement of Indonesia's global reputation. Methods: This study uses primary and secondary data approaches, which entail gathering data with common tools and focusing on observable and interpretable outcomes. The primary data is derived from the author's professional experience and an online validation survey, while the secondary data is gathered through library research of journals, reports, and official publications to support the qualitative analysis. Findings: Without having an impact on the national economy, the MICE sector will generate a lot of jobs and help the general public prosper. However, the study also identifies critical challenges, including heavy reliance on government budgets, pervasive gender inequality in leadership, and the urgent need for sustainable waste management protocols. Conclusion: The study concludes that the MICE industry’s resilience depends on a strategic shift toward financial independence from government funding and the institutionalization of gender equality in leadership. Novelty/Originality of this article: This study offers a novel integrated framework for the MICE sector by bridging the gap between digital-era operational efficiency and often-overlooked socio-environmental dimensions, such as gender equity and sustainable waste mitigation.